What matters most: Qualitative investigation of goals and values in a diverse sample of patients with advanced cancer. Issue 28 (1st October 2022) - Aller, Ashley; Shirazi, Aida; Altschuler, Andrea; Hauser, Karen; Martinez, Francisco; Katzel, Jed Abraham; Lin, Amy Ying Ju; Jones, Tyler; Lim, Peggy T; Yen, Sue May; Whitehead, Hannah; Liu, Raymond
Abstract : 252 Background: Goals of care conversations (GOCC) are a complex part of patient-focused care. Current understanding of GOCC content is limited to post-hoc patient satisfaction surveys and focus groups evaluating end-of-life advance care planning physician-patient interactions, and documentation. We investigated patient goals and values through standardized GOCC documentation by oncologists in patients with advanced cancer. Methods: This pilot qualitative analysis of patient goals and values included all adult patients > 18 years with advanced recurrent or stage IV cancer seen at Kaiser Permanente San Francisco with an oncologist documented GOCC between 1/1/2022 to 5/14/22. Our team developed a templated GOCC automated phrase (Smartphrase) within our electronic medical record (EMR), with a selection tab that included a listing of common patient goals and values and an option to add free text. Team members reviewed each patient's initial GOCC content was reviewed for frequently occurring themes consistent with goals and values. Results: A total of 178 patients had EMR documented GOCC, with a mean of 1.8 GOCC per patient. These patients were 51% (n = 94) female, with a median age of 68.5 years old. The population was racially diverse with 46% identifying as White, 32% Asian/Pacific Islander, 13% Black, 8% Hispanic/Latino, and 1% Other. The most common cancer types included breast (19%, n = 34), lower GI (16%, n = 29), and thoracic (14%, n = 25). Family members were present in 35% (n = 63) of GOCC. Table summarizes thematically grouped goals and values. Conclusions: Our findings highlight the importance of GOCC in routine oncology visits. Our standardized documentation tool for GOCC prompted medical oncologists to identify what matters most to patients with advanced or recurrent cancer regarding their values and goals related to care and quality of life. Among the wide range of responses, we identified that the most important goals and values to our patients include avoiding pain and suffering, physical independence, and living as long as possible. In contrast, patients rarely identified comfort-only treatment as a priority. This tool can guide goal-concordant care at initial onset of the cancer journey and be revisited as these conversations evolve over time. Future investigation is needed to understand how GOCC goals and values identified early impact patient satisfaction, change over time, influence treatment decisions, and potentially lead to an evolution in standard for goal-concordant care.Goals and values within initial standardized EMR GOCC documentation. Goals and Values Number of Responses (% of patients) Avoid Pain and Suffering 71 (40%) Physical Independence 69 (39%) Living as Long as Possible 68 (38%) Mental Clarity 39 (22%) Ability to Communicate 34 (19%) Avoid or Minimize Being in the Hospital 17 (10%) Comfort Focused Treatment Only 6 (3%) Total Number of Responses 304